113 Analyzing conflicts between biological and economic efficiencies of beef production without mature cows. (7th December 2018) - Harrison, M; Seidel, G; Ahola, J; Rhoades, R; Mooney, D
Abstract: Confounding interests between biological and economic efficiencies of the All Heifer, No Cow (AHNC) beef production system makes system evaluation difficult. In a conventional cow/calf system, emphasis is placed on reproduction, longevity, and maternal behavior with the goal of achieving a cow that successfully breeds back and consistently weans a healthy calf each year. With AHNC, calving ease and carcass quality are emphasized. In the AHNC system, yearling heifers are inseminated with sexed semen to produce primarily females; calves are weaned 3 months after parturition; heifers are finished on a high concentrate diet; and are harvested before 30 months of age. By eliminating the mature cowherd, every animal in the enterprise is growing, offering improved biological efficiency. However, the reduction in feed use does not necessarily equate with economic efficiency. The carcasses produced are high marbling, but payment does not always reflect quality due to premature bone ossification caused by increased hormone concentrations during pregnancy. A model was developed using system dynamics methodology to simulate an AHNC production system. The objective was to increase understanding of interactions and trade-offs between biological and economic efficiencies in the AHNC system. Biological efficiency was considered as lifetime kg of TDN (input) per kg of hot carcass weight produced (output). Profitability was evaluated using net income. The model was calibrated using data from the period 2013 to 2017 collected from the management of an AHNC herd. Efficiency was evaluated by changing the age at harvest and adjusting diet type. Profit leverage points were identified by changing selected variables ±10 % from the observed values while all other variables were held constant. Net income was sensitive to the percent female calves born; a greater number of females coincide with greater profitability. Results suggested AHNC could be managed to balance biological and economic efficiency.